The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3813/aaa.918605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sounds from Water on Perception of Acoustic Environments Dominated by Road-Traffic Noise

Abstract: As acomplement to conventional noise mitigation, addition of wanted sounds, in particular sounds from water structures, has been suggested as am ethod for improving noise-polluted acoustic environments. The effect of adding water sounds to road-trafficn oise wase xplored in al istening experiment with 31 listeners. Recordings of road-trafficnoise were combined with recordings of waters sounds of varying pleasantness, and the listeners assessed the sounds on eight adjective scales, representing the perceptual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 32 publications
4
37
0
4
Order By: Relevance
“…Two components were found regarding soundscape perception; component 1 explained around 50% of the variance, while component 2 showed 20% of explained variance. Similar to the previous study (Kawai et al 2004;Berglund and Nilsson, 2006;Viollon and Lavandier, 2000;Axelsson et al, 2010;Rådsten-Ekman et al, 2013), component 1 was related to pleasantness including the adjectives pleasant, calm, chaotic, and annoying. Component 2 consisted of eventful, uneventful, exciting, and monotonous represented by the perception of eventfulness.…”
Section: Principal Component Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…Two components were found regarding soundscape perception; component 1 explained around 50% of the variance, while component 2 showed 20% of explained variance. Similar to the previous study (Kawai et al 2004;Berglund and Nilsson, 2006;Viollon and Lavandier, 2000;Axelsson et al, 2010;Rådsten-Ekman et al, 2013), component 1 was related to pleasantness including the adjectives pleasant, calm, chaotic, and annoying. Component 2 consisted of eventful, uneventful, exciting, and monotonous represented by the perception of eventfulness.…”
Section: Principal Component Analysissupporting
confidence: 71%
“…Pearson's correlation coefficients between the spatial function for a tranquil place and the acoustic elements in (a) the cathedral and (b) Buddhist temple precincts (*p < 0.05, **p < 0.01). (Axelsson et al, 2010;Rådsten-Ekman et al, 2013). In terms of audio-visual effect on tranquility, it was found that the effects of sound and visual environment on tranquility were similar even though the contribution of visual attractiveness was slightly larger than sound pleasantness in the cathedral precincts; the standardized multiple regression coefficients were 0.42 and 0.53, respectively.…”
Section: B Factors Influencing Tranquility In Urban Religious Spacementioning
confidence: 84%
“…The adjectives have been identified as the characteristics of soundscape quality in previous studies, one of the most commonly used of which is pleasantness 13,14,45 . For the perceptual assessment of traffic noise, perceived annoyance is an important and frequently examined characteristic 1,4,46,47 .…”
Section: Participants and Evaluation Proceduresmentioning
confidence: 99%
“…Natural sounds, such as birdsong and water sounds, which may benefit people's relaxation in urbanised areas, 9 have been studied frequently, with particular considerations for their interaction with common urban noise, e.g., road traffic noise. 10,11,12,13 As a result, the concept of "masking" has re-emerged within the scope of soundscape because masking effects have been demonstrated to have considerable effects on the quality of soundscape. 6,14,15 Furthermore, due to the crucial role of human visual-aural interaction in sound environment However, in real-life soundscapes, the roles of sound source perception and cognition are highly relevant to masking effects.…”
Section: Iintroductionmentioning
confidence: 99%
“…Dubois [12] and Nilsson and Berglund [10] found a neutral impact of human sounds on the soundscape quality. For natural sounds, it seems that bird songs have a positive influence whatever the context but water sounds with temporal variability may have a positive influence whereas water sounds with high loudness and low temporal variability may have a negative influence on pleasantness [13][14][15][16]. In that frame, several researches studied the link between soundscape quality and relevant perceptual dimensions with regression models [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%